Percent Disability Change in the Time - İnce, Cengiz Haluk (The Bulletin of Legal Medicine, 2004)
There have been numerous problems both in the assessment and percent calculation of disability in Turkey. Computation of the ratio of loss of working capacity is made according to various laws and regulations. It seems that the problem of assessment arise from incomplete or wrong determination of malfunction of injured area in occupational accident. It is therefore essential that is fair both to the victim and employer. This study is to point out at the differences and deficiencies in the computation of the degree of disability and at the necessity to bring common standardize to these computations. The purpose of this paper is to present injury leading to disability and illustrate how a percent, age is calculated correctly. Key words: Disability, Occupational accident, Percent calculation of disability, Turkey